Correlation Between Ability on Playing Tetris and GPA - Aprilia Ratna Christanti; Yulianto Tejo P. (SISFORMA, 2014)
The goal of this study is to determine the correlation between ability on playing Tetris and GPA of Soegijapranata Catholic University, Department of Information System students against the dexterity in playing Tetris. The research has been done using experiment method on ten Information System students who have various grade points. They played Tetris, 30 minutes each, for three consecutive days. The results showed that: First, eight out of the ten students improved their agility. It can be seen from the increasing scores and levels; Second, the coefficient correlation between student grade point and dexterity in playing Tetris is by 62%.Keywords Ability, grade point average, Tetris